The Political Economy of North American Free Trade
XV, 348 p.
Keywords: Analyzes the economic, social, political and environmental implications of NAFTA from a range of critical perspectives. The chapters, unified by a sceptical view of the management of economic integration in North America cover the economic strategy of Mexico, Canada-US trade agreement and more.